Bahasa Inggris - Baiq Meiranti Eka Putri; Baharuddin Baharuddin; Santi Farmasari (Universitas Nahdlatul Wathan Mataram, 2023)
This article is aimed at determining the accuracy of post-editing translations on GNMT by English Department students. The objects of this study were students of the English Education Study Program, Faculty of Teacher Training and Education, University of Mataram, who were admitted to the